Public Health as a Social Science: Reflections on the Possibilities of a Comprehensive Public Health - Claudio Baeza (GoAcademica Research & Publishing, 2020)
Close historic relationships between medicine and public health have implied, as a consequence for the latter, the in-heritance of epistemological traits traditionally characteristic of a positivistic conception of science on which a major part of the theoretical development of modern medicine has been sup-ported. From the point of view of this ontological, epistemological and methodological reference of positivism, health has been reduced to deterministic, linear and causalistic explanations that systematically cancel any reference to the life world (Lebenswelt), both for the researcher and for the “objects” of research. The scientific pretensions of public health have become protruding over its political and ethical commitment, even widening the gap between scientific knowledge and the specific conditions of existence of social actors and their relation to health. This paper presents some reflections around the conditions of possibility for a comprehensive approach of public health problems. These reflections are based on a conception of health as a social phenomenon, that is to say, as an emergent element from the complex web of inter-subjective relationships among social actors, in a specific social and historic horizon. Epistemological, ethical and political implications of this perspective for research in public health are also discussed.